Group Incidence by Purulent-Septic Infections of Clebsiellous Etiology in Cardiosurgical Patients - V. I. Sergevnin; L. G. Kudryavtseva; O. G. Pegyshina; E. O. Volkova; N. I. Reshetnikova (Эпидемиология и вакцинопрофилактика, 2020)
Relevance. In surgical hospitals, outbreaks of purulent-septic infections (GSI) caused by Klebsiella pneumonia do often occur. The causes of such outbreaks generally remain insufficiently clear. The purpose of the work is an epidemiological diagnostics of group incidence by GSI clebsiellous etiology, which arose in cardiosurgical hospital.Materials and methods. The analysis K. pneumonia eduction frequency and detection of purulent-septic infection Klebsiella etiology among patients of anaesthesiology and reanimation department and treatment departments of a cardiosurgical hospital in 10 months 2019 was carried out. Against the background of increased frequency of a bacteria carrying 13 strains of K. pneumonia were genotyped, their adhesive activity, ensitivity to 29 antibiotics and to three disinfectants (D) were studied.Results. According to the results of agent genotyping, 5 epidemic centers of clebsiellous purulent-septic infection etiology with 11 cases of infection were detected. All K. rheumoniae strains found in epidemic focus were polyresistant to antibiotics and in 46.1% of cases resistant to Q.A.C. containing disinfectant. The circumstance of formation of related cases of purulent septic infection in certain epidemic centers was simultaneous stay of sick in anaesthesiology and reanimation department with the presence of common personnel.Conclusion. The spread of infection in the conditions of anaesthesiology and reanimation department of the cardiac hospital most likely occurred because of a contact-household path involving intermediate factor of the transmission of the pathogen.